2016
DOI: 10.1002/jmri.25570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neonatal brain myelination using the T1‐ and T2‐weighted MRI ratio

Abstract: 2 Technical Efficacy: Stage2 J. MAGN. RESON. IMAGING 2017;46:690-696.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 32 publications
2
51
0
1
Order By: Relevance
“…All the included participants fulfilled the following inclusion criteria: (1) complete clinical data (including demographic information, origin T1-MPRAGE, T2-FLAIR and PET imaging, and histological diagnosis); and (2) performance of lesionectomy. The following patients were excluded: (1) patients who were less than 3 years old, as the myelination of the neonatal brain does not reach maturity (Soun et al, 2016), which may influence imaging data normalization; (2) patients with low-quality images resulting from head motion, noise or other image artifacts; and (3) patients with FCD III on histopathology, as other principle lesions may affect the performance of the artificial neural network (ANN).…”
Section: Methodsmentioning
confidence: 99%
“…All the included participants fulfilled the following inclusion criteria: (1) complete clinical data (including demographic information, origin T1-MPRAGE, T2-FLAIR and PET imaging, and histological diagnosis); and (2) performance of lesionectomy. The following patients were excluded: (1) patients who were less than 3 years old, as the myelination of the neonatal brain does not reach maturity (Soun et al, 2016), which may influence imaging data normalization; (2) patients with low-quality images resulting from head motion, noise or other image artifacts; and (3) patients with FCD III on histopathology, as other principle lesions may affect the performance of the artificial neural network (ANN).…”
Section: Methodsmentioning
confidence: 99%
“…Although the T1w/T2w ratio is not a direct index of myelin, it is nevertheless considered a surrogate marker of myelin content [29]. This method was initially developed to evaluate intra-cortical myelin [29][30][31], and myelination of white matter in neonatal brains has also been investigated using this method [32]. The test-retest reliability of the T1w/T2w ratio has been reported to be high [33] and a histological study of patients with MS has shown that the T1w/T2w ratio in the cortex differed significantly between early-stage MS and healthy controls [34].…”
Section: Introductionmentioning
confidence: 99%
“…Although T 1 w/T 2 w ratio is not a direct index of myelin, it is still considered a proxy of myelin content 36 . While intracortical myelin content across different ages has been evaluated using this method 36 , 37 , myelination of white matter (WM) in neonatal brains has also been investigated using this method 38 , 39 . Further, the test-retest reliability of T 1 w/T 2 w ratio has been reported to be high 40 .…”
Section: Introductionmentioning
confidence: 99%